Dialektika Dakwah Minoritas Muslim di Pakuwon City Surabaya - Aziz, Moh. Ali; Subandi, Bambang (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This article reports on research conducted in 2018 about the dialectic of Muslim minority da'wah in the multicultural-metropolitan community in Pakuwon City Surabaya, using a qualitative descriptive approach. Findings illustrate Muslim minority in Pakuwon City has a strong religious identity and the pleasure of ukhuwah Islamiyah. This is supported by the central role of the commodification agent, namely takmir (mosque committee) of the Al-Madani mosque. In additin, Muslim minority in Pakuwon City makes the Al-Madani mosque a center for da'wah through oral, written, and social movement methods, such as religious sermon, religious forum, web-based media, zakat and qurban, and fundraising for social services. Another finding reveals that the dialectic proselytising of Muslim minority in the multicultural-metropolitan community in Pakuwon City Surabaya produces a symmetrical environmental harmony which is in line with the satisfaction of the da'wah partners.